Hubungan Kecanduan Game Online dengan Pola Tidur Remaja SMA Negeri 1 Kupang Saat Pandemi COVID-19 - Jelita, Tiara; Takaeb, Afrona E. L.; Ndoen, Enjelita M. (Yayasan Literasi Sains Indonesia, 2023)
Playing online games has a positive impact but also has a negative impact on adolescents, especially to disrupted sleep patterns. This research endeavors to elucidate the correlation between online gaming addiction and sleep patterns among adolescents attending SMA Negeri 1 Kupang during the COVID-19 pandemic. This research adopts an analytical survey design with a cross-sectional approach. The sample comprises 308 individuals, selected through a simple random sampling technique. The data analysis was conducted using Chi-square test with a significance level (α) of 5%, and the data processing using the SPSS software. The research findings revealed that male respondents experienced a higher prevalence of online gaming addiction (71.1%). The reason cited by respondents for playing online games was to alleviate the stress. The research findings among addicted gamer respondents revealed that the majority had been playing online games for more than 3 years (34%), the most used gadget for gaming was a smartphone (99%), the most popular online game played was Mobile Legend (39.2%), the time most used to accessed online games was at evening (82.5%). Regarding the playing duration, the most range was 1-3 hours (44.3%) and the highest frequency of gameplay was daily (47.4%). The research findings indicate that out of 97 respondents addicted to online gaming, 57 individuals (58.8%) experienced disrupted sleep patterns. The statistical Chi-square test resulted in a p-value of 0.003. This indicates that there is a relationship between online gaming addiction and sleep patterns among adolescents attending SMA Negeri 1 Kupang during the COVID-19 pandemic.